‘Right Now, Sophie ∗Swims in the Pool?!’: Brain Potentials of Grammatical Aspect Processing - Flecken, Monique; Walbert, Kelly; Dijkstra, Ton (Frontiers in Psychology, 2015)
We investigated whether brain potentials of grammatical aspect processing resemble semantic or morpho-syntactic processing, or whether they instead are characterized by an entirely distinct pattern in the same individuals. We studied aspect from the perspective of agreement between the temporal information in the context (temporal adverbials, e.g., Right now) and a morpho-syntactic marker of grammatical aspect (e.g., progressive is swimming). Participants read questions providing a temporal context that was progressive (What is Sophie doing in the pool right now?) or habitual (What does Sophie do in the pool every Monday?). Following a lead-in sentence context such as Right now, Sophie…, we measured ERPs time-locked to verb phrases in four different conditions, e.g., (a) is swimming (control); (b) *is cooking (semantic violation); (c) *are swimming (morpho-syntactic violation); or (d)?swims (aspect mismatch); …in the pool”. The collected ERPs show typical N400 and P600 effects for semantics and morpho-syntax, while aspect processing elicited an Early Negativity (250-350 ms). The aspect-related Negativity was short-lived and had a central scalp distribution with an anterior onset. This differentiates it not only from the semantic N400 effect, but also from the typical (L)AN (Left Anterior Negativity), that is frequently reported for various types of agreement processing. Moreover, aspect processing was not accompanied by a clear P600 modulation. We argue that the specific context for each item in this experiment provided a trigger for agreement checking with temporal information encoded on the verb, i.e., morphological aspect marking. The aspect-related Negativity obtained for aspect agreement mismatches reflects a violated expectation concerning verbal inflection (in the example above, the expected verb phrase was Sophie is X-ing rather than Sophie X-s in condition d)). The absence of an additional P600 for aspect processing suggests that the mismatch did not require additional reintegration or processing costs. This is consistent with participants’ posthoc grammaticality judgements of the same sentences, which overall show a high acceptability of aspect mismatch sentences.